PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN DISPOSISI MATEMATIS SISWA BERBANTUAN GEOBOARD KELAS VII SMP SWASTA AL MANAR MEDAN - Anggi Ramadani Simatupang; Siti Maysarah (LPPM Universitas Bina Bangsa, 2024)
The purpose of this study is to determine the validity, practicality and effectiveness of learning tools developed based on the discovery lerning model to improve the ability to understand concepts and mathematical dispositions of geoboard-assisted students. Researchers use the development method or R&D (research and development) with a 4-D model (four-D) developed by Thiagarajan, Semmel and Semmel. Which includes the process of define, design, develop, and disseminate stages. The subjects in this study were grade VII students of Al Manar Medan Private Junior High School. From the results of field trials, it can be concluded that: 1) learning devices that meet the validity criteria with a very valid predicate with each RPP average value is 4.61, Module is 4.56, and LAS is 4.58, 2) practical learning tools based on the validation results from the expert team have met the validity with a little revision and the results of interviews with students / users get positive responses, 3) meet the effectiveness criteria based on the results of the concept comprehension ability test meet classical completeness with a value of 86.36%, the results of teacher observations managing learning have been effective because of the increase from the first meeting to the last meeting, the results of achieving the ideal percentage of time interval are at the threshold of time tolerance of predetermined categories, and from the results of the mathematical disposition ability questionnaire it is concluded that all aspects get a positive response